Respuesta :
Answer is =-1
implifying
-2x + 3 = -3x + 2
Reorder the terms:
3 + -2x = -3x + 2
Reorder the terms:
3 + -2x = 2 + -3x
Solving
3 + -2x = 2 + -3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3x' to each side of the equation.
3 + -2x + 3x = 2 + -3x + 3x
Combine like terms: -2x + 3x = 1x
3 + 1x = 2 + -3x + 3x
Combine like terms: -3x + 3x = 0
3 + 1x = 2 + 0
3 + 1x = 2
Add '-3' to each side of the equation.
3 + -3 + 1x = 2 + -3
Combine like terms: 3 + -3 = 0
0 + 1x = 2 + -3
1x = 2 + -3
Combine like terms: 2 + -3 = -1
1x = -1
Divide each side by '1'.
x = -1
Simplifying
x = -1
Subract 2 from bothsides to get -2x + 1 = -3x
Add 2x to both sides to get 1 = -1x
Divide both sides to get -1 = x
Since the values aren't the same (like, it doesn't say -1 = -1 or x = x), it isn't infinite. It doesn't say 0=x so it's not no solution.
This means that it's one solution because only one value can equal x